The Oman Botanic Garden (3): : a Review of Progress (2010–2016) with Emphasis on Herbarium and Seed Bank Collections, Propagation Challenges and Garden Design Principles - Lupton, Darach (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2017)
This article follows two others published in Sibbaldia in 2008 and 2009 about the development of Oman Botanic Garden (OBG) and highlights the subsequent progress of key elements of the collection. Significant revisions to the design of OBG are discussed, as are developments in landscape design principles and aspirations. The growth and management of the OBG herbarium and seed bank collections and propagation department are described, with a focus on on operational challenges and achievements. Numerical data are presented to demonstrate the growth in all three departments, and images of facilities and species in the collections are shown. The overarching challenges, achievements and ambitions for the future of OBG are conveyed throughout.